Harmful organisms of alfalfa crop and their control measures - Alimboyeva Salomat Maqsad girl (Genius Publishing Group, 2022)
The article describes the harmful organisms of the alfalfa crop and measures to combat them.
Keywords: Application; populations; considered; northernmost